Leachate analysis of trace metals from e-waste disposed of in landfills and open dumps - Nascimento, Gabriela de Almeida [UNESP]; Souza, Ricardo Gabbay de [UNESP]; Fiore, Fabiana Alves [UNESP]; Dantas de Jesus, Amanda Maria [UNESP] (Elsevier, 2024)
Waste electrical and electronic equipment (WEEE, or e-waste) has been largely generated worldwide, but the estimated proportion of WEEE that undergoes the correct disposal is very low. The objective of this study was to evaluate e-waste trace metals in the leachate from disposal of WEEE in soil, using different analytical approaches to determine how these methods may interfere in the results. Different forms of WEEE and MSW landfilling and open dumping were simulated in column reactors to analyse the resultant leachates. Analyses of heavy metals in the leachates were performed in two ways: via inductively coupled plasma-mass-spectrometry with acid digestion of samples, following American Standard 3015A, and via inductively coupled plasma-optical emission spectrometry without acid digestion (US Environmental Protection Agency - USEPA, 2007). Metal concentrations found in the landfill and dumping simulations were similar, but a higher concentration of metals was found in samples with e-waste content, and those undergoing acid digestion prior to ICP analyses. Exceptions were Ba e Zn with a higher concentration without digestion, what may indicate the appearance of matrix effect. Concentrations of Pb, Cu and Mn in the leachates indicate possible interference with MSW. Additionally, it was evident that the timescale of observation influenced the results.
Keywords: Heavy metals; Landfill; Leachate; Open dumps; WEEE